Penerapan Sistem Pendukung Keputusan Dalam Penilaian Kinerja Supervisor Dengan Menggunakan Metode Maut Dan Pembobotan Entropy - Devi, Wanda Tofani; Mesran, M; Siregar, Annisa Fadillah (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
Position positions in PT. Bintang Mutiara Cemerlang is a supervisor, where the problem in this company is the supervisor's performance appraisal process which is less effective because it is seen based on the length of work alone, causing injustice to other supervisors who have not worked long enough. Therefore, a decision support system is created that is capable of supporting the performance appraisal procedure. This decision support system applies the MAUT method and the Entropy method to the process to see the value obtained in the system. Each criterion has its own weight so that the alternatives can be ranked. The MAUT (Multi Attribute Utility Theory) method is a quantitative method in which there are structured stages to find out and describe the variables in it. After ranking, the results obtained from the application of the MAUT and Entropy methods are the A10 alternative on behalf of Shadad Putra S.H with a value of 0.84060 as the best alternative in assessing supervisor performance at PT. Shining Pearl Star.